2006
DOI: 10.1002/polb.20917
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state NMR characterizations on phase structures and molecular dynamics of poly(ethylene‐co‐vinyl acetate)

Abstract: Solid-state nuclear magnetic resonance spectroscopy and relaxation measurements, together with DSC, have been used to elucidate the structures and molecular dynamics in poly(ethylene-co-vinyl acetate) (EVA). It has been found that besides immobile orthorhombic and monoclinic crystalline phases, the third mobile crystalline phase (possibly the phase) of a considerable amount (36% of total crystalline phases) appears in the EVA samples, which forms during room-temperature aging as a result of the secondary cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 45 publications
(74 reference statements)
1
41
0
1
Order By: Relevance
“…However, no well-resolved reflections from monoclinic phase and SOCP phase were detected by WAXD at room temperature. 30,31 This is conformed by our experiment results of WAXD as shown in Table III, the grain size L hkl (Å ) of (110) crystal plane of various EAA/ EVA blends is listed. It is observed that the L hkl of (110) crystal plane has the same tendency to increase with the hot air aging time, which indicates the completion of secondary crystallization.…”
Section: Hot Air Aging On Crystallization Behavior Of Eaa/eva Blendssupporting
confidence: 74%
“…However, no well-resolved reflections from monoclinic phase and SOCP phase were detected by WAXD at room temperature. 30,31 This is conformed by our experiment results of WAXD as shown in Table III, the grain size L hkl (Å ) of (110) crystal plane of various EAA/ EVA blends is listed. It is observed that the L hkl of (110) crystal plane has the same tendency to increase with the hot air aging time, which indicates the completion of secondary crystallization.…”
Section: Hot Air Aging On Crystallization Behavior Of Eaa/eva Blendssupporting
confidence: 74%
“…From a critical perspective, there does not seem to be any piece or pieces of evidence that could not be explained either by water absorption and/or slow crystallization of ethylene segments. Further, this same peak at $508C that grows with room temperature annealing occurs in both unneutralized acid copolymers [112] as well as other ethylene copolymers, [113][114][115], although the effect is not nearly as dramatic. The best way to prove that such a transition exists is to choose a system that cannot crystallize, and rigorously exclude water to eliminate these two possible explanations.…”
Section: Ionomer Synthesismentioning
confidence: 96%
“…For the spin 3/2 nucleus of 23 Na, the solid-state NMR signal of 23 Na was recorded with half of the liquid-state NMR 90°pulse length (i.e., 1.75 ls corresponding to 90°pulse length for central-selective excitation) (Causemann et al 2011). The 23 Na spinlattice relaxation time in the rotating frame (T 1q ) was measured using a spin-lock pulse sequence (Wang et al 2006).…”
Section: Nmr Measurementsmentioning
confidence: 99%